2012
DOI: 10.4038/sjdem.v1i1.4181
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in pregnancy among Sri Lankan women: gestational or pre-gestational?

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…A higher GDM prevalence in Asians has been demonstrated in the literature previously. Some publications have also shown evidence of worse outcome in Asian PGDM subjects compared to their GDM counterparts (Ferrara, 2007; Jayathilaka, Dahanayake, Abewardhana, Ranaweera, & Rishard, 2012; Shefali, Kavitha, Deepa, & Mohan, 2006) Our findings suggest that races with the highest predilection for diabetes during pregnancy may not necessarily have the highest racial predilection for type 2 or type 1 DM. To our knowledge, this is the first time that such racial/ethnic comparisons have been made between PGDM and GDM in a single population.…”
Section: Discussionsupporting
confidence: 52%
“…A higher GDM prevalence in Asians has been demonstrated in the literature previously. Some publications have also shown evidence of worse outcome in Asian PGDM subjects compared to their GDM counterparts (Ferrara, 2007; Jayathilaka, Dahanayake, Abewardhana, Ranaweera, & Rishard, 2012; Shefali, Kavitha, Deepa, & Mohan, 2006) Our findings suggest that races with the highest predilection for diabetes during pregnancy may not necessarily have the highest racial predilection for type 2 or type 1 DM. To our knowledge, this is the first time that such racial/ethnic comparisons have been made between PGDM and GDM in a single population.…”
Section: Discussionsupporting
confidence: 52%
“…Lwanga and Lemeshow equation 15 was used for the sample size calculation. According to previous study findings prevalence of GDM in Sri Lankan population was 18% 5 . Expected sensitivity for this study was 75% and expected specificity was 95%.…”
Section: Methodsmentioning
confidence: 84%
“…According to the world diabetes report published by the WHO in 2016, second highest prevalence of GDM is reported among the south East Asian countries including Sri Lanka 4 . Prevalence of GDM in Sri Lanka, in year 2014 was 18% 5 in 2016 prevalence of GDM in urban and suburban areas of Sri Lanka was reported as 13.8% 6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, majority of patients in our study (88.8%) underwent post prandial blood sugar (PPBS) during the booking visit. A previous study conducted in Anuradhapura district in 2012 (8), used urinary sugar level which is not very reliable or accurate as the screening test. Compared to that we observed a marked improvement in diagnostic practice in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…IADPSG (the international association of the diabetes and pregnancy study groups) criteria had a good predictive value for macrosomia in a Sri Lankan study (7). A study conducted in Anuradhapura district found that random urine sugar tests were done as the screening test for hyperglycaemia in pregnancy in 93% and blood sugar levels were done in less than 41% (8). However random urine sugar test and fasting blood sugar test were found to be unreliable in another Sri Lankan study and they suggested that 2-hour blood sugar level after 75 g of oral glucose had better sensitivity and speci city for diagnosis of diabetes mellitus in early pregnancy (9).…”
mentioning
confidence: 99%